Unraveling the closet: Exploring reflective decluttering and its implications for long-term sufficient clothing consumption - Samira Iran; Cosette Joyner Martinez; Lisa Sophie Walsleben (Cleaner and Responsible Consumption)
The growing trend of decluttering has spurred many consumers to streamline their wardrobes by removing excess garments. However, garment decluttering has not received much attention in the academic research. This study employs a mixed methods approach to explore how reflective garment decluttering can be related to sufficient clothing consumption by investigating 1) consumers’ motivations to declutter and the methods used, 2) the influence of reflective decluttering on consumers' perceptions of their clothing items and consumption habits, and 3) the impact of reflective decluttering on long-term clothing acquisition and strategies for maintaining sufficient clothing consumption. Qualitative analysis reveals that motivations for decluttering include reducing garment over-ownership, creating space, and finding emotional relief. Participants gained insights into the value of their garments, their reasons for possession, and their consumption habits, helping them establish future consumption goals. Quantitative findings from a longitudinal survey add to the qualitative insights by showing that reflective decluttering was associated with reduced clothing acquisition, although a slight rebound occurred after six months. The qualitative findings also reveal strategies including conscious shopping and extending garment life cycles that reduce consumption levels and promote sufficiency-oriented practices over time.